Assessment of Zoonotic Pathogens in Poultry and Environmental Water Sources Using Duplex PCR in Karbala, Iraq (Indian Journal of Animal Production and Management, 2025)
Background The world-wide poultry industry has grown rapidly to provide the  increasing demand for low-cost protein. This expansion offers more opportunities  for zoonotic diseases to be transmitted, especially Salmonella spp. and Vibrio cholerae that are important pathogens for foodborne illness. Both Salmonella has been  reported among poultry flocks in Karbala, Iraq and V. cholerae which is commonly  associated with contaminated water may also represent potential zoonotic risk within  the settings of poultry production. Culture-based detection is time-consuming,  laborious and may fail to detect low levels of contamination; molecular methods like  the polymerase chain reaction (PCR) provide fast, sensitive and specific identification  of targets that are amenable for large epidemiological surveys. Objective:  To investigate the molecular prevalence of Salmonella spp. and Vibrio cholerae in  the different samples, their concurrent occurrence, assess associated risk factors and  estimate the performance of duplex PCR assay for pathogens monitoring. Methods:  Descriptive study of 20 poultry farms in Karbala province was conducted over a  period of one year. In total, 82 samples were collected from the hens and cloaca swabs  of poultry and feces samples (n = 82) and environmental/water (n = 118). Isolation  and detection of Salmonella was based on invA gene and V. cholerae using rtxA/lolB  genes by duplex PCR; results were confirmed through agarose gel electrophoresis.  Chi-squared tests and logistic regression were used to determine prevalence  and associations with potential risk factors, including farm biosecurity and quality of  water source. Results: Salmonella spp. was found in 15% of poultry, mainly in cloacal  swab indicating extensive carrier status. Vibrio cholerae was detected in 9% of water/ environment samples. Simultaneous presentation of both pathogens was found in 6%  of waterborne samples, indicating possible cross-contamination predominately from  water. Pathogen occurrence was positively correlated with low biosecurity and use  of natural water sources (P < 0.05). The duplex PCR showed excellent sensitivity and  specificity to rapid diagnosis. Conclusion: This study provides valuable molecular  epidemiological evidence regarding the prevalence and cross-resistance of Salmonella and V. cholerae in Karbala region. The biosecurity and water management should  be strengthened, and routine surveillance with duplex PCR is needed to prevent  resistance zoonotic risks and public health protection. Serotyping of Salmonella and  determination of V. cholerae toxicity need to be added in future studies to further  assess public health risks.
Keywords: Salmonella, Vibrio cholerae, Poultry, Water sources, Molecular epidemiology, Duplex PCR, Karbala, Zoonotic pathogens.